THE STUDY OF KALDOR HYPOTHESIS FOR TURKEY BY VAR ANALYSIS - SARI , Sultan (SSD Journal, 2022)
According to Kaldor Hypothesis, the growth of the GDP is related to the growth of the manufacturing sector. Kaldor claims that the productivity of the manufacturing sector is positively related the growth of the manufacturing sector and labour force transfer from agriculture and like other sector which marginal productivity of labour force is lower than average productivity level to manufacturing sector under Industrial growth model, and by increasing labour force productivity, it leads to increase production, in other word, GDP.In the study, for Turkey, this relationship between growth and manufacturing production, under Kaldor’s first law of growth, is considered by VAR analysis and with quarterly data between 2007 and 2021. As expected, there are positive relationship between industrial production and growth. It means that industrial production leads to economic growth. However, it is not seen any causality relationship from growth to industrial production. One direction positive relationship from industrial production to growth is confirmed by Granger causality test. As known, while impulseresponse functions indicate the serials response direct to any shock(s), variance decomposition indicates how total changes are share relatively by serials during periods. According to analysis, it can be claimed that any transfer can take 1 year on explaining total changes between serials.